Reconstituted cryopreserved platelets synthesize proteins during short‐term storage and packaging a defined subset into microvesicles. Issue 9 (14th June 2021) - Schubert, Peter; Johnson, Lacey; Culibrk, Brankica; Chen, Zhongming; Tan, Shereen; Marks, Denese C.; Devine, Dana V.
Abstract: Background: Cryopreservation of platelets (PLTs) could allow extension of their shelf‐life to years, compared to days for liquid stored platelets. Due to their greater hemostatic effect, reconstituted cryopreserved platelets (cryo‐PLTs) would be able to support bleeding emergencies. Since protein synthesis has been linked to PLT functions, such as clot formation and immune responses, the translational capacity of reconstituted cryo‐PLTs was assessed upon thawing and short‐term storage. Methods/materials: Platelets were frozen at −80°C with 5–6% DMSO. Upon thawing, they were reconstituted in plasma and then aliquoted (12 ml) into mini‐bags and assessed over 24 h of storage at RT. One series served as control; the second and third series were spiked with either 300 μM puromycin (Pm) or 227 nM biotin‐labeled Pm. Samples were tested for in vitro quality and PLT microvesicle enumeration by flow cytometry. Protein synthesis in cryo‐PLTs was assessed using a modified method based on puromycin‐associated nascent chain proteomics. Results: In vitro parameters of reconstituted and subsequently stored platelets were consistent with previously published results. Mass‐spectrometry analyses identified that 22 proteins were synthesized in PLTs and 13 of those were observed in platelet microvesicles (PMVs). Conclusion: Cryo‐PLTs can synthesize proteins upon reconstitution and storage. Discovery of a subset of these proteins in the PMV suggests a role in vesicle encapsulation, possibly in a selective manner. This observation provides novel insights into the capacity for protein synthesis in cryo‐PLTs and the potential regulation of protein packaging into PMV.